2015
DOI: 10.1038/jcbfm.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

The Gothenburg MCI study: Design and distribution of Alzheimer’s disease and subcortical vascular disease diagnoses from baseline to 6-year follow-up

Abstract: There is a need for increased nosological knowledge to enable rational trials in Alzheimer's disease (AD) and related disorders. The ongoing Gothenburg mild cognitive impairment (MCI) study is an attempt to conduct longitudinal indepth phenotyping of patients with different forms and degrees of cognitive impairment using neuropsychological, neuroimaging, and neurochemical tools. Particular attention is paid to the interplay between AD and subcortical vascular disease, the latter representing a disease entity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 88 publications
0
104
0
2
Order By: Relevance
“…The Gothenburg MCI study is an ongoing prospective clinical longitudinal study with a fixed study protocol focusing on the cognitive, neurochemical, brain structural and clinical course of incipient and manifest stages of cognitive disorders such as dementia (see Wallin et al [19] for a full description). Participants undergo biennial comprehensive examinations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gothenburg MCI study is an ongoing prospective clinical longitudinal study with a fixed study protocol focusing on the cognitive, neurochemical, brain structural and clinical course of incipient and manifest stages of cognitive disorders such as dementia (see Wallin et al [19] for a full description). Participants undergo biennial comprehensive examinations.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for sampling and analysis of CSF has been previously described [19]. A ‘CSF AD profile' was calculated using the formula (Aβ 42 /p-tau > 3.694 + 0.0105 × T-tau) presented by Mattsson et al [30] which has been shown to predict, with good diagnostic accuracy, which MCI patients will progress to AD.…”
Section: Methodsmentioning
confidence: 99%
“…Vascular dementia is another cause of cognitive impairment, considered to be the second most common form of dementia after Alzheimer’s disease and is observed in about 30 % of all dementia patients. Recently, an overlap between Alzheimer’s disease and vascular dementia with small vessel disease has been reported as a possible contributor and cause of dementia [1113]. Cerebral amyloid angiopathy and hypertensive arteriopathy constitute the two most common small vessel diseases and are thought to be important parts of the dementia disease process [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…All participants took part in the Gothenburg MCI study [10]. They had been enrolled in the study if they were between 50 and 79 years of age and if they presented with self-reported and/or informant-reported cognitive decline with a duration of at least 6 months, as assessed in a clinical interview, without obvious relation to somatic or psychiatric disorders or trauma.…”
Section: Methodsmentioning
confidence: 99%
“…The level of WMC was determined using a modified version of the Fazekas scale [19]. See the publication by Wallin et al [10] for a detailed description of diagnostic procedures.…”
Section: Methodsmentioning
confidence: 99%